2000
DOI: 10.5144/0256-4947.2000.202
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of Fever in Children

Abstract: Background: Fever is a common medical problem in children which often prompts parents to seek immediate medical care. The objective of this study was to survey parents about their knowledge and attitude concerning fever in their children. Patients and Methods:The study involved the random selection of Saudi parents who brought their febrile children to the emergency rooms or walk-in clinics of four hospitals in Riyadh. Parents of 560 febrile children were interviewed using a standard questionnaire to obtain so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 14 publications
7
77
1
5
Order By: Relevance
“…Previous studies, performed in acute care settings in secondary care, showed a range of 44-84% of parents not knowing the correct definition of fever (>38˚C). 6,[14][15][16] Generally, it is known that parents' knowledge about fever and antipyretics is poor. 17 This is in line with the present finding that almost one in three of the parents thought that every child with a fever needs to be treated with paracetamol or antibiotics.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Previous studies, performed in acute care settings in secondary care, showed a range of 44-84% of parents not knowing the correct definition of fever (>38˚C). 6,[14][15][16] Generally, it is known that parents' knowledge about fever and antipyretics is poor. 17 This is in line with the present finding that almost one in three of the parents thought that every child with a fever needs to be treated with paracetamol or antibiotics.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…1 Youssef et al also reported that parents have high fear of fever related complication and 35% parents believed that it can Cause brain injury. 6 This was attributed to the facts that in their study majority of parents had more than 2 children and were of more than 30 year of age.…”
Section: Awarenessmentioning
confidence: 93%
“…This difference might be due low level of illiteracy among the mothers in studied population of Arab. 6 In 1998 in United Kingdom Blumenthal surveyed 392 parents. He found that 30% of parents could not define normal temperature.…”
Section: Awarenessmentioning
confidence: 99%
See 2 more Smart Citations